Primary aggressive osteosarcoma of sphenoid bone - Che Jalil, Nur Asyilla; Baba, Farahlina; Zaidin, Ahmad Hadif; Abdullah, Mohamad Muhaimin; Bakrin, Ikmal Hisyam; Ghani, Abdul Rahman Izani; Mat Zin, Anani Aila (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Osteosarcoma is a malignant intra-osseous neoplasm producing osteoid. Osteosarcoma of the skull is very rare and it usually involves the cranial vault. The occurrence in the skull base is extremely rare. We report a case of primary osteosarcoma in 59-year-old lady, occur in left sphenoid wing with intracranial and intranasal extension manifesting as left facial pain, headache and left epistaxis. She underwent radiotherapy as the surgical resection of the tumour is not feasible due to the critical extent of the tumour. We describe the clinical, radiological and histopathological findings of the case.